(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Mortuary is an important area where not only autopsies are conducted or bodies are preserved but it is the place where Humanitarian Forensic is actually practiced. Autopsies are very crucial in Indian justice system but at the same time basic infrastructure for the mortuary do have an important role in increasing efficiency of people working in and also to minimize negative perception of relatives of the deceased during their emotional distress. Having an ideal mortuary set up is challenging in developing country like India but still there are many institutes who are role models in highlighting importance of mortuary services. Just having good quality autopsy tables, air conditioning system, etc. are not sufficient but the factors like location, infrastructure, layout, facilities, laboratories, environmental and engineering aspects, etc. cannot be ignored. At some places, the mortuary lacks even the most basic amenities like washrooms, proper sitting area, basic autopsy equipments etc. Due to the lack of maintenance, mortuary’s general atmosphere is dismal and unpleasant. Considering these factors, we discussed here on the set up of mortuary complex designed at our institute.